Tanggungjawab Orangtua Dalam Membentuk Kepribadian Anak Perspektif Alquran dan Psikologi - Zakiati Salma (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article aims to find out how the Qur'anic guidance on the role of parents in building the child's character and review it through the psychology view. Translation of the meaning of the Quranic verses cited using the method of Tafsir Maudhu'i. The result of the discussion found that there are three responsibilities of parents in building the child's personality in the Qur'an, 1) Responsibility of faith education, contained in the QS. At-Tahrim [66]: 6; 2) Responsibility of morals education, contained in the QS. Luqman [31] verse 18-19; 3) The Responsibility of intellectual education, contained in the QS. Ash-Shaffat [37] verse 102. This concept is reinforced by the theory of developmental psychology that believes that a child's final outcome is determined by three things: parent factors, educational factors, and environmental factors